Dynamics of Resolving Gross Human Rights Violations in Aceh - Muhammad Ghozali; Rais Aufar; Cut Afra; T Samsul Bahri; M Agra Dwadima; Ramalinggam Rajamanickam (International Journal of Law, Social Science, and Humanities, 2025)
Following the peace agreement in Aceh in 2005, Indonesia through Law Number 11 of 2006 established the legal basis for the establishment of the Aceh Truth and Reconciliation Commission (TRC), with the aim of addressing human rights violations that occurred during the conflict. The TRC was mandated to formulate recommendations for reparations for victims, but although these recommendations have been formulated, their implementation has not been fully implemented. This study reveals that although reparation recommendations have been made, their implementation is highly dependent on the policies and decisions of the Aceh Government, which can then delegate implementation to related institutions based on the urgency and needs of the victims.